1997
DOI: 10.1074/jbc.272.41.25429
|View full text |Cite
|
Sign up to set email alerts
|

The Activated Form of the Lck Tyrosine Protein Kinase in Cells Exposed to Hydrogen Peroxide Is Phosphorylated at Both Tyr-394 and Tyr-505

Abstract: Members of the Src family of non-receptor tyrosine protein kinases are known to be inhibited by the intramolecular association between a phosphorylated carboxyl-terminal tyrosine residue and the SH2 domain. We have previously shown that exposure of cells to H 2 O 2 strongly activates Lck, a lymphocyte-specific Src family kinase, by inducing phosphorylation on Tyr-394, an absolutely conserved residue within the activation loop of the catalytic domain. Here we show that Lck that has been activated by H 2 O 2 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 40 publications
3
54
1
Order By: Relevance
“…At least for Jurkat T cells it was described that Tyr 394 /Tyr 505 doubly phosphorylated Lck was catalytically active, demonstrating that phosphorylation of the positive regulatory site Tyr 394 is dominant over the C-terminal inhibitory Tyr 505 phosphorylation (38). In line with this finding, the significant FRET increase of our Y394F-mutated biosensor in comparison to the parental construct shows the strong mechanical link between the activation loop and the overall conformation of Lck in living cells.…”
Section: Discussionsupporting
confidence: 75%
“…At least for Jurkat T cells it was described that Tyr 394 /Tyr 505 doubly phosphorylated Lck was catalytically active, demonstrating that phosphorylation of the positive regulatory site Tyr 394 is dominant over the C-terminal inhibitory Tyr 505 phosphorylation (38). In line with this finding, the significant FRET increase of our Y394F-mutated biosensor in comparison to the parental construct shows the strong mechanical link between the activation loop and the overall conformation of Lck in living cells.…”
Section: Discussionsupporting
confidence: 75%
“…Once autophosphorylated on Y a , Src becomes hyperactive regardless of the phosphorylation status of Y r , although Y r can still be phosphorylated to form the doubly phosphorylated form. In support of this model, Lck that is phosphorylated on both Y a and Y r and hyperactive was recently isolated from Jurkat human leukemic T cells (Hardwick and Sefton, 1997). Csk phosphorylation can only inactivate Src that is not autophosphorylated.…”
Section: Discussionmentioning
confidence: 93%
“…Thus it is possible that p56 lck -induced ROI generation mediates the activation of NF-B, AP-1, JNK, MEK, and apoptosis. H 2 O 2 has been shown to activate p56 lck enzyme (38), but whether p56 lck can mediate ROI generation, has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that ROI are also required for HIV-tat-induced cellular responses (18). Moreover p56 lck has been shown to be a redox-sensitive protein kinase (38). Whether p56 lck is required for the ligand-induced generation of ROI is not known.…”
Section: Roi Inductionmentioning
confidence: 99%